The Effectiveness of the Window Shopping Strategy in Improving Students’ Learning Outcomes in Durūs al-Lughah at Pondok Pesantren Miftahul Huda Suko in the Academic Year 2025-2026 - Fitri Setyo Rini; Ifa Rodifah Nur; Vava Ulil Albab (CV Putra Publisher, 2026)
Arabic instruction in the second grade of Pondok Pesantren Miftahul Huda Suko is still dominated by the conventional lecture method, which is passive and teacher-centered, causing many students to struggle to understand the material and to lack motivation. This study aims to determine the effectiveness of the Window Shopping strategy in improving students’ learning outcomes in Durūs al-Lughah (Arabic language lessons). It employed a quantitative quasi-experimental method with a time series design, involving 25 second-grade students selected through purposive sampling. Data were collected through achievement tests administered four times before the strategy (pretest) and four times after it (posttest), and analyzed with SPSS 27 using the Friedman test, repeated-measures ANOVA with the Greenhouse-Geisser correction, and a paired-sample t-test. The results showed that the mean score increased from 63.60 in the pretest to 82.90 in the posttest, a gain of 19.30 points. The significance value (Sig. = 0.001 < 0.05) indicated a statistically significant improvement, and the effect size (Cohen’s d = 2.095) fell within the very large category. The standard deviation also declined after the treatment, indicating more homogeneous outcomes. Thus, the Window Shopping strategy is proven effective in Arabic language learning, as it improves learning outcomes while fostering students’ activeness, cooperation, and critical thinking skills.